Gender diversity in pediatric surgery: academic ranks and scholarly productivity amongst pediatric surgeons - Mullis, Danielle M.; Mueller, Claudia; Bonham, Spencer A.; Hunt, Emily; Uribe, Daniela; Miller, Hayley; Bianco, Y. Katherine (Frontiers in Surgery, 2024)
Despite a growing number of women entering medical school, a small proportion of women pursue surgical specialties, including pediatric surgery. This multi-center study assesses gender-based differences in measures of scholarly productivity and distribution of faculty positions.This is a retrospective web-based study of all pediatric surgeons at twelve large institutions across the United States. Data published by the American Association of Medical Colleges was compiled and analyzed to understand the gender distributions of medical students, general surgery residents, and pediatric surgery fellows. P-values were calculated using twosided Student's independent t-tests and chi-squared tests.There have been a growing number of women applying into pediatric surgery, but the proportion of women matriculating into these fellowships is not concordant. Women are still underrepresented (28%) amongst the pediatric surgeon workforce. A total of 111 pediatric surgeons were identified for this study, which included 31 women (28%) and 80 males (72%). There was a significant difference in the distribution across academic ranks between genders (p<0.001). Women had significantly fewer publications per year after residency, fewer total publications, and a lower h-index in comparison to men (p<.001, p=.005, p=.002, respectively).Women are not only underrepresented in pediatric surgery, but there are also significant differences in the distribution of faculty positions and scholarly productivity when comparing men and women. There is a pressing need to improve gender diversity and identify barriers that may prevent women from advancing to leadership positions and achieving professional success.